An advanced data fabric architecture leveraging homomorphic encryption and federated learning - Rieyan, Sakib Anwar; News, Md. Raisul Kabir; Rahman, A.B.M. Muntasir; Khan, Sadia Afrin; Zaarif, Sultan Tasneem Jawad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.